Does living in a community with more educated mothers enhance children's school attendance? Evidence from Sierra Leone - Kamanda, Mamusu; Madise, Nyovani; Schnepf, Sylke (International Journal of Educational Development, 2016)
In Sierra Leone girls are 23.4% less likely to attend secondary education than boys. This difference between sexes increases the gender gap in educational attainment since women's education is positively associated with children's educational wellbeing. This paper investigates the relationship between children's school attendance, their mothers’ level of education, as well as the overall level of women's education at the community level in Sierra Leone using multilevel statistical modelling techniques and the country's 2008 Demographic and Health Survey data. The findings suggest that, regardless of a child's own mother's education, an increase in the proportion of mothers with secondary or higher education in a community by 10% improves the probability of attending junior secondary school significantly by 8%; a 50% increase improves the likelihood of attending school by 45%. There was no significant relationship between the proportion of better educated mothers in a community and primary school attendance. However, relative to children whose mothers had no formal education, children whose mothers had attained primary, secondary or higher education were 7%, 14% and 22% more likely to attend primary school respectively. Future policies should seek to promote girls’ education at post-primary education and develop community based programmes to enable the diffusion and transmission of educational messages.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2015.09.008 2405685:YPUYEULY
Keywords: Girls’ education; Mothers’ education; School attendance; Sierra Leone

Donor policies in post-war Sierra Leone - Kanyako, Vandy (Journal of Peacebuilding & Development, 2016)
The Sierra Leone peace process following the country's 1991–2002 civil war between the Government of Sierra Leone (GoSL) and the Revolutionary United Front (RUF) benefited immensely from the energetic involvement of an eclectic mix of donors. Traditional inter-governmental financial institutions and relatively new private funding foundations all channelled aid money and technical expertise through various multilateral and bilateral mechanisms for rebuilding the country. Without a doubt Sierra Leone's recovery from the debilitating 11-year war would not have come to pass in the time and manner it did without the robust intervention of such funders. Based on fieldwork conducted in Sierra Leone at the height of the peacebuilding process, this article outlines the role played by international donors in rebuilding post-war Sierra Leone. It posits that understanding the modus operandi of the assorted mix of donor agencies in creating the country's aid architecture is key to grasping the nuances of the Sierra Leone peace process. This is partly because the aid largesse, though well intentioned, was injected into a barely functioning system that lacked a coherent recipient regime. The article concludes that though donors were critical to Sierra Leone's rebuilding efforts, their lack of emphasis on a needs-centred funding mechanism created an inadequate model to address the country's complex post-war reconstruction challenges.
Publisher: SAGE Publications Inc KerkoCite.ItemAlsoKnownAs: 10.1080/15423166.2016.1146035 2339240:EC6LW5LV 2405685:IHKCCGSR

Reconstructing education in post-conflict Sierra Leone - Pai, Grace (Security, Education and Development in Contemporary Africa, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:83TRVQZR

Education in Emergencies Endline Evaluation Report – Sierra Leone - Sankoh, Didan; Cowan, Emma (Girls' Education Challenge, UK Aid, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:G2I2A3Y5

Open Data Readiness Assessment: Prepared for the Government of Sierra Leone - Chrzanowski, Pierre; Holm, Jeanne; Manley, Laura; Dodds, Elizabeth; Baker, Rob (World Bank Group; Open Aid Partnership, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:83I8VUFY

Final Evaluation of the Project: Increasing Access, Retention and Performance in Primary Education: Implemented by Child to Child & the Pikin-To-Pikin Movement Kailahun District, Sierra Leone, 2011-2016 - Institute for Development (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:3E624NH3 2405685:5LVXNGJZ 2405685:CRQUMLFF

Education Needs Assessment Report - Sierra Leone - Plan International (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:FPBLY982 2486141:T8M7TVMD

Continental Education Strategy For Africa (2016 – 2025) - African Union (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:EH4P26FW

Ethiopia Growth and Transformation Plan II (GTP II) | Green Growth Knowledge Platform - Ethiopia National Planning Commission (Federal Democratic Republic of Ethiopia, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:XG2MRXIK

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets